GIS-based risk assessment of typhoon disasters in coastal provinces of China - Wang, Yebao; Liu, Wenhao; Chen, Chuntao; Li, Xiaoqing; Liu, Baijing; Du, Peipei; Sheng, Shanzhi (Frontiers in Marine Science, 2025)
Typhoons pose a significant threat to China’s coastal regions, resulting in substantial economic losses and casualties. Understanding the vulnerability of these areas to typhoon stress is crucial for effective disaster management and risk mitigation. This study assesses the vulnerability of China’s coastal provinces to typhoon disasters by integrating three key factors: exposure, sensitivity, and adaptability. The primary methodologies employed are the Analytic Hierarchy Process (AHP) and Geographic Information System (GIS) techniques. A comprehensive risk assessment framework is developed using 17 indicators, with AHP applied for indicator weighting and GIS used for spatial analysis and visualization of vulnerability patterns. The findings indicate considerable spatial variation in vulnerability, with southern provinces such as Guangdong, Guangxi, and Hainan exhibiting high vulnerability due to frequent typhoons, dense populations, and lower adaptive capacity. Southeastern regions, like Fujian and Zhejiang, show moderate to high vulnerability, while northern provinces such as Jiangsu, Hebei, and parts of Shandong and Liaoning experience lower vulnerability, attributed to reduced exposure and stronger disaster preparedness systems. These results underscore the importance of targeted disaster management strategies tailored to the specific vulnerabilities of each region.